2016
DOI: 10.3733/ca.v070n02p71
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for potassium and magnesium in irrigation water quality assessment

Abstract: Irrigation with treated wastewater is expected to increase significantly in California during the coming decade as a way to reduce the impact of drought and mitigate water transfer issues. To ensure that such wastewater reuse does not result in unacceptable impacts on soil permeability, water quality guidelines must effectively address sodicity hazard. However, current guidelines are based on the sodium adsorption ratio (SAR) and thus assume that potassium (K) and magnesium (Mg), which often are at elevated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 29 publications
0
26
0
2
Order By: Relevance
“…The power source indicates a supply of fresh material from surrounding areas. The primary ions indicate the alkalinity of water (Oster et al 2016 ). Sulfates formed during organic decay are then evidence of water contamination.…”
Section: Introductionmentioning
confidence: 99%
“…The power source indicates a supply of fresh material from surrounding areas. The primary ions indicate the alkalinity of water (Oster et al 2016 ). Sulfates formed during organic decay are then evidence of water contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that, in addition to sodium, exchangeable potassium and magnesium can also increase soil swelling and dispersion affecting soil physical properties [11][12][13][14][15]. The effects of these cations in causing swelling and dispersion are not similar, but depend on the ionicity index [14], a molecular scale geochemical parameter which estimates the relative bonding (ionic and covalent) tendency of a cation with charged particles.…”
Section: Ion Exchange and Resultant Soil Structural Stabilitymentioning
confidence: 99%
“…The cation ratio of soil structural stability CROSS (Table 1) expands and modifies SAR to account for the dispersive properties of K + and to more precisely account for the flocculating capacity of Mg 2+ relative to Ca 2+ . The U.S. Salinity Laboratory [4] originally introduced the potassium adsorption ratio PAR to account for the dispersive properties of K + but the PAR was largely ignored as a water quality parameter until the introduction of CROSS [5,8].…”
Section: Parametermentioning
confidence: 99%